PELAKSANAAN TUGAS KESEHATAN KELUARGA PADA SUKU MINANGKABAU DI DESA NOGO REJO KECAMATAN GALANG TAHUN 2021 - HELENA FRANSYSCA (JURNAL ILMIAH MAKSITEK, 2021)
The family has a health duty whose purpose is to prevent the occurrence of health problems and care for sick familymembers. There are five health tasks that must be done by the family dengan well. The implementation of this family healthtask is inseparable from the cultural factors owned by the family, such as the Minangkabau tribe who adhere to the patrilinealsystem. This research aims to identify the implementation of family health tasks in the Minangkabau tribe in Nogo RejoVillage of Galang Subdistrict. Research design is descriptive. Sampling with purposive sampling technique. A sample of 46people consisted of 28 male respondents and 18 female respondents. The study was conducted from September 17 toNovember 12, 2021. Data collection is done using a questionnaire of family health tasks that includes demographic data andfamily health tasks. Then the data obtained is processed using descriptive analysis to determine the distribution offrequencies and percentages. The results showed that almost two-thirds (2/3) of respondents carried out family health dutiesin the Minangkabau tribe with a good category (63.04%). The conclusion of this study shows that implementing family healthduties in the Minangkabau tribe belongs to the category of good (63.04%).